Deaths due to accidental submersion in southern Brazil - Novais, Rafael Brendo; Murrugarra , Lais Kaori Sato; Luz, Kelly Cristina Suzue Iamaguchi; Frez , Flávia Cristina Vieira; Oliveira, Isabelly Leal de; Sesnik, Heitor Hortensi; Murilho, Jordhan Abner Teixeira; Dias, Giovana Munhoz; Santos , Gabriel Vale dos; Sanches , Rafaely de Cássia Nogueira; Uema, Roberta Tognollo Borotta; Sanguino, Gabriel Zanin (Seven Editora, 2023)
Introduction: Drowning is the alteration of respiratory function at the level of the trachea, bronchi or lungs, through airway obstruction resulting from submersion/immersion in a liquid medium. The main risk factors for drowning include alcohol and drug use, lack of swimming skills, and a variety of circumstances, including natural disasters and maritime incidents. Drowning mostly happens in children under the age of five, adolescents under the age of 15, and the elderly. Objective: To identify and understand the rates of deaths due to accidental submersion in adults in the southern region of Brazil in 2021. Method: This was a descriptive exploratory study with a quantitative approach. Data collection took place through access to the Ministry of Health's health data platform DATASUS, in the Tabnet health information tab originating from the Mortality Information System (SIM). Results and discussion: In 2021, 79 deaths due to drowning were identified in the southern region of Brazil. Of these, 67 (85%) were male and 12 (15%) were female. Regarding male deaths, 37 (47%) occurred in the hospital and 30 (39%) were identified at home. For females, 4 (33%) deaths occurred in the hospital and 8 (67%) at home. There was a prevalence for both sexes and in both environments, whether hospital or home, they are adults between 20 and 59 years old, with a mean age of approximately 38 years, and most of the time associated with the lack of appropriate supervision. The predominance in relation to race/color was white, with an average of 100% for females, and 49 males (73%), followed by 24% for brown race/color and 3% for black race/color. Conclusion: The incidence of deaths from drowning in the southern region of Brazil in 2021 was higher among hospitalized adult men aged 20 to 59 years, according to literary information. It is understood that drowning is a public health problem and that the spheres of power should spare no effort to reduce the number of deaths from this preventable cause. DOI:https://doi.org/10.56238/sevened2023.004-009